Association of monthly allowance with body-mass index and body image perception among students - Mohd Ali, Nor Syifa; Mohd Shukri, Nor Azwani; Khattak, Muhammad Muzaffar Ali Khan (Med Crave, 2020)
Introduction: It is well documented fact that there are differences in the actual and perceived body image among both sexes. This study was aimed to assess the association of monthly allowance with body-mass index (BMI), and body image perception among university students. Methods: The design of this study was a cross sectional design A total of 152 students were registered from the International Islamic University Malaysia, Kuantan Campus. A questionnaire administered comprised of three sections i.e. socio-demographic, anthropometric and body image perception data using Figure Rating Scale (FRS) & Shape Questionnaire (BSQ). The collected data on the three aspects were compiled and statistically analyzed using descriptive analysis and Pearson correlation analysis. Results: The statistical analysis revealed that there was no association between the student students’ allowance and body image perception, however, still using considerable amount of their allowances for looking good. The FRS assessment shows that the respondents perceived degree of self-discrepancy between current and ideal body image. The body image perception assessed with BSQ showed the respondents are least concern about body shape. However, there was significant P<0.05) association between body-mass index (BMI) and body image perception assessed with FRS and BSQ. Conclusions: This study indicates that there is a general trend among the students that when their BMI increases consequently their body image satisfaction decreases. Therefore, it can be inferred that the students spend considerable amount of their stipend on looking good and due to the miss-perception of body image satisfaction.